Exploring cell death mechanisms in liver transplantation: implications for graft survival - Hirao, Hirofumi; Watanabe, Takeshi; Uchida, Yoichiro; Hatano, Etsuro (Frontiers in Immunology, 2026)
Liver transplantation (LT) has become a life-saving therapy for patients with end-stage liver disease and malignancies. However, graft survival remains a significant challenge because of LT-related stresses. Grafts are subject to several stresses, including cold preservation after procurement and during transportation, as well as warm ischemia until vascular reconstitution, which can trigger hepatic cell death. This review examines the various cell death mechanisms that influence liver graft outcomes, including apoptosis, necrosis, autophagy, and non-apoptotic inflammatory cell death. We discuss how these mechanisms are driven by ischemia-reperfusion injury, which contributes to graft dysfunction. Apoptosis leads to the selective elimination of damaged hepatic cells, while necrosis, resulting from fulminant injury, can provoke inflammatory responses that further jeopardize graft viability. Autophagy emerges as a double-edged sword, promoting cellular repair under stress while potentially leading to cell death in extreme circumstances. Additionally, recent studies have uncovered novel non-apoptotic death pathways, such as necroptosis, pyroptosis, ferroptosis, panoptosis, and netosis, that may also influence transplant outcomes. Understanding the intricate interplay of these cell death mechanisms is vital for developing innovative therapeutic strategies to enhance graft survival. By synthesizing current research findings, this review aims to highlight the potential for targeted interventions to mitigate cell death and improve liver transplant outcomes, ultimately improving patient survival and quality of life.